Role of Transforming Growth Factor-β1 in Regulating Fetal-Maternal Immune Tolerance in Normal and Pathological Pregnancy - Yang, Dongyong; Dai, Fangfang; Yuan, Mengqin; Zheng, Yajing; Liu, Shiyi; Deng, Zhimin; Tan, Wei; Chen, Liping; Zhang, Qianjie; Zhao, Xiaomiao; Cheng, Yanxiang (Frontiers in Immunology, 2021)
Transforming growth factor-β (TGF-β) is composed of three isoforms, TGF-β1, TGF-β2, and TGF-β3. TGF-β1 is a cytokine with multiple biological functions that has been studied extensively. It plays an important role in regulating the differentiation of immune cells and maintaining immune cell functions and immune homeostasis. Pregnancy is a carefully regulated process. Controlled invasion of trophoblasts, precise coordination of immune cells and cytokines, and crosstalk between trophoblasts and immune cells play vital roles in the establishment and maintenance of normal pregnancy. In this systematic review, we summarize the role of TGF-β1 in regulating fetal-maternal immune tolerance in healthy and pathological pregnancies. During healthy pregnancy, TGF-β1 induces the production of regulatory T cells (Tregs), maintains the immunosuppressive function of Tregs, mediates the balance of M1/M2 macrophages, and regulates the function of NK cells, thus participating in maintaining fetal-maternal immune tolerance. In addition, some studies have shown that TGF-β1 is dysregulated in patients with recurrent spontaneous abortion or preeclampsia. TGF-β1 may play a role in the occurrence and development of these diseases and may be a potential target for the treatment of these diseases.